2010
DOI: 10.1063/1.3483872
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-wave generation via frequency multiplication in graphene

Abstract: In this letter, we demonstrate that a graphene monolayer, over which three metallic electrodes forming a coplanar waveguide are patterned, acts as a frequency multiplier and generates frequencies at least up to 40 GHz. These results show that monolayer graphene is a natural frequency multiplier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 14 publications
4
59
0
1
Order By: Relevance
“…In [14], a frequency multiplier is demonstrated with a graphene sample shunting the signal trace and ground planes of a CPW line. However, power dependence effect is not studied.…”
Section: B Nonlinear Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In [14], a frequency multiplier is demonstrated with a graphene sample shunting the signal trace and ground planes of a CPW line. However, power dependence effect is not studied.…”
Section: B Nonlinear Characterizationmentioning
confidence: 99%
“…This results from the linear dispersion of the carriers in graphene, instead of the parabolic dispersion of conventional semiconductors. Some works have reported demonstration of frequency multiplier and mixer at microwave frequency range [14][15][16]. However, no systematic microwave nonlinear property study on graphene has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, M. Dragoman developed a millimeter wave graphene frequency multiplier based on CPW using the nonlinear electromagnetic characteristics of graphene, and had verified the nonlinear theory of graphene firstly [11]. In 2011, R. Camblor developed a tripler using microstrip gap loaded with multilayer graphene [6].…”
Section: Introductionmentioning
confidence: 99%
“…The paper shows that the reflection parameter of the antenna can be tuned by a DC voltage. 2D radiation patterns at various frequencies in the X band (8)(9)(10)(11)(12) are then presented using as antenna backside a microwave absorbent and a metalized surface. Although the radiation efficiency is lower than a metallic antenna, the graphene antenna is a wideband antenna while the metal antennas with the same geometry and working at the same frequencies are narrowband.…”
mentioning
confidence: 99%
“…Few examples are graphene field-effect transistors (FETs) with f max ¼ 70 GHz, 7 graphene FETs with cutoff frequencies in the THz range, 8,9 microwave and millimeter wave generation via multiplication, 10 even graphene receivers at microwave frequencies, 11,12 and THz frequencies. 13,14 The antennas are key components in any wireless communication system.…”
mentioning
confidence: 99%